A mathematical model of intracellular behavior of microalgae for predicting growth and intracellular components syntheses under nutrient‐replete and ‐deplete conditions. Issue 10 (25th July 2018) - Ryu, Kyung Hwan; Sung, Min‐Gyu; Kim, Boeun; Heo, Seongmin; Chang, Yong Keun; Lee, Jay H.
Abstract: Microalgae is a promising biomass source for renewable fuels and chemicals production. To describe microalgal behavior and improve their cultivation, various kinetic models have been proposed. However, previous works have focused on biomass formation and lipids production only, even though carbohydrates and proteins are also important products, not only for understanding the metabolic behavior of microalgae but also for enhancing the economic viability through value‐added side products. In this study, a new mathematical model is proposed to explain core biological mechanisms of growth and macromolecules syntheses based on the central metabolism of carbon and nitrogen. In the model, microalgal growth is separated as hyperplasia and hypertrophy, to describe the cell growth more precisely under nutrient‐replete and ‐deplete conditions. Sensitivity analysis performed using the model indicates that cell state (e.g., cell death rate) has a strong effect on the lipid production explaining the difficulty of reproducing a microalgae culture experiment. Abstract : A new mathematical model for microalgae describing the core biological mechanism of growth and macromolecules (i.e., protein, carbohydrate, and lipid) syntheses based on the central metabolism of carbon and nitrogen was developed. The proposed model expressed cell growth as two separate types of hyperplasia and hypertrophy to describe the cellular behavior in response to the external culture condition. By using the proposed model, microalgal behaviors under the nutrient‐replete/‐deplete condition were well explained.